Answer:
-3
Step-by-step explanation:
We want (n/p)(1). We can obtain this by finding n(1) and p(1) and then dividing as indicated:
p(1) = 3(1) - 2 = 1
n(1) = 2(1) - 5 = -3
Then (n/p) (1) = -3/1, or just -3
Answer:
1. y = -2x+5
2. y = 3/4 - 3
3. intercept = -5 slope = 4/3
4. intercept = 1 slope = -1/2
Answer:
c) (![(6-\sqrt{12} )(6+\sqrt{12} ) = 24](https://tex.z-dn.net/?f=%286-%5Csqrt%7B12%7D%20%29%286%2B%5Csqrt%7B12%7D%20%29%20%3D%2024)
d) (
Step-by-step explanation:
<u><em>Step(i):-</em></u>
Given that the binomial expression
(![(6-\sqrt{12} )(6+\sqrt{12} )](https://tex.z-dn.net/?f=%286-%5Csqrt%7B12%7D%20%29%286%2B%5Csqrt%7B12%7D%20%29)
Multiply
( 36 + 6√12 -6√12 -(√12)²)
= ( 36 -12)
= 24
c) (![(6-\sqrt{12} )(6+\sqrt{12} ) = 24](https://tex.z-dn.net/?f=%286-%5Csqrt%7B12%7D%20%29%286%2B%5Csqrt%7B12%7D%20%29%20%3D%2024)
<u><em>Step(ii):- </em></u>
Given that the binomial expression
(
Multiply
= 9 - 3√8 + 3√8 -(√8)²
= 9 - 8
= 1
d) (